Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.

Homogeneous photochemical water oxidation by biuret-modified Fe-TAML: evidence of Fe-V(O) intermediate - Panda, Chakadola; Debgupta, Joyashish; Diaz, David Diaz; Singh, Kundan K.; Gupta, Sayam Sen; Dhar, Basab B. (Journal of the American Chemical Society, 2014)
{Water splitting, leading to hydrogen and oxygen in a process that mimics natural photosynthesis, is extremely important for devising a sustainable solar energy conversion system. Development of earth-abundant, transition metal-based catalysts that mimic the oxygen-evolving complex of photosystem II, which is involved in oxidation of water to O-2 during natural photosynthesis, represents a major challenge. Further, understanding the exact mechanism, including elucidation of the role of active metal-oxo intermediates during water oxidation (WO), is critical to the development of more efficient catalysts. Herein, we report Fe-III complexes of biuret-modified tetra-amidomacrocyclic ligands (Fe-TAML; 1a and 1b) that catalyze fast, homogeneous, photochemical WO to give OD with moderate efficiency (maximum TON = 220

Mechanism of oxygen atom transfer from Fe-V(O) to olefins at room temperature - Singh, Kundan K.; Tiwari, Mrityunjay K.; Dhar, Basab B.; Vanka, Kumar; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
In biological oxidations, the intermediate Fe-V(0)(OH) has been proposed to be the active species for catalyzing the epoxidation of alkenes by nonheme iron complexes. However, no study has been reported yet that elucidates the mechanism of direct O-atom transfer during the reaction of Fe-V(0) with alkenes to form the corresponding epoxide. For the first time, we study the mechanism of O-atom transfer to alkenes using the Fe-V(0) complex of biuret-modified Fe-TAML at room temperature. The second-order rate constant (k(2)) for the reaction of different alkenes with Fe-V(0) was determined under single-turnover conditions. An 8000-fold rate difference was found between electron-rich (4-methoxystyrene; k(2) = 216 M-1 s(-1)) and electron-deficient (methyl transcinnamate; k(2) = 0.03 M-1 s(-1)) substrates. This rate difference indicates the electrophilic character of Fe-V(0). The use of cis-stilbene as a mechanistic probe leads to the formation of both cis- and trans-stilbene epoxides (73:27). This suggests the formation of a radical intermediate, which would allow C-C bond rotation to yield both stereoisomers of stilbene-epoxide. Additionally, a Hammett rho value of -0.56 was obtained for the para-substituted styrene derivatives. Detailed DFT calculations show that the reaction proceeds via a two-step process through a doublet spin surface. Finally, using biuret-modified Fe-TAML as the catalyst and NaOCl as the oxidant under catalytic conditions epoxide was formed with modest yields and turnover numbers.

Electrocatalytic water oxidation by a molecular cobalt complex through a high valent cobalt oxo intermediate - Das, Debasree; Pattanayak, Santanu; Singh, Kundan K.; Garai, Bikash; Sen Gupta, Sayam (Chemical Communications, 2016)
Biuret-modified tetraamidomacrocyclic cobalt complex [Co-III-bTAML]- is shown to catalyze electrochemical water oxidation at basic pH leading to the formation of O-2. Electrochemical and spectroscopic studies indicate a high valent cobalt oxo intermediate isoelectronic to Co-V(O) as the active oxidant. The kinetic isotope effect of 8.63 indicates an atom proton transfer mechanism.

Electrochemical formation of Fe-V (O) and mechanism of its reaction with water during O-O bond formation - Pattanayak, Santanu; Chowdhury, Debarati Roy; Garai, Bikash; Singh, Kundan K.; Paul, Amit; Dhar, Basab B.; Sen Gupta, Sayam (Chemistry-A European Journal, 2017)
A detailed electrochemical investigation of a series of iron complexes (biuret-modified tetraamido iron macrocycles FeIII-bTAML), including the first electrochemical generation of Fe-V(O), and demonstration of their efficacy as homogeneous catalysts for electrochemical water oxidation (WO) in aqueous medium are reported. Spectroelectrochemical and mass spectral studies indicated FeV(O) as the active oxidant, formed due to two redox transitions, which were assigned as Fe-IV(O)/Fe-III(OH2)and Fe-V(O)/Fe-IV(O). The spectral properties of both of these high-valent iron oxo species perfectly match those of their chemically synthesised versions, which were thoroughly characterised by several spectroscopic techniques. The O-O bond-formation step occurs by nucleophilic attack of H2O on FeV(O). A kinetic isotope effect of 3.2 indicates an atom-proton transfer (APT) mechanism. The reaction of chemically synthesised Fe-V(O) in CH3CN and water was directly probed by electrochemistry and was found to be first-order in water. The pK(a) value of the buffer base plays a critical role in the rate-determining step by increasing the reaction rate several-fold. The electronic effect on redox potential, WO rates, and onset overpotential was studied by employing a series of iron complexes. The catalytic activity was enhanced by the presence of electron-withdrawing groups on the bTAML framework. Changing the substituents from OMe to NO2 resulted in an eightfold increase in reaction rate, while the overpotential increased threefold.

Reductive activation of O-2 by a bioinspired Fe complex for catalytic epoxidation reactions - Singh, Kundan K.; Sen Gupta, Sayam (Chemical Communications, 2017)
Aerobic epoxidation of olefins catalyzed by iron complexes without the use of a sacrificial coreductant is unknown. We report the reductive activation of O-2 by a bioinspired [(bTAML)Fe-III(H2O)](-) (1) complex to catalyze the epoxidation of alkenes with TONs of up to 80. Spectroscopic and kinetic evidence indicates the involvement of FeV(O) as the active oxidant during the reaction.

Spectroscopic and reactivity comparisons of a pair of bTAML complexes with Fe-V=O and Fe-IV=O units - Pattanayak, Santanu; Jasniewsk, Andrew J.; Rana, Atanu; Draksharapu, Apparao; Singh, Kundan K.; Weitz, Andrew; Hendrich, Michael; Que, Lawrence, Jr.; Dey, Abhishek; Sen Gupta, Sayam (Inorganic Chemistry, 2017)
In this report we compare the geometric and electronic structures and reactivities of [Fe-V(O)](-) and [Fe-IV(O)](2-) species supported by the same ancillary nonheme biuret tetraamido macrocyclic ligand (bTAML). Resonance Raman studies show that the Fe-O vibration of the [Fe-IV(O)](2-) complex 2 is at 798 cm(-1), compared to 862 cm(-1) for the corresponding [Fe-V(O)](-) species 3, a 64 cm(-1) frequency difference reasonably reproduced by density functional theory calculations. These values are, respectively, the lowest and the highest frequencies observed thus far for nonheme high-valent Fe-O complexes. Extended X-ray absorption fine structure analysis of 3 reveals an Fe-O bond length of 1.59 angstrom, which is 0.05 angstrom shorter than that found in complex 2. The redox potentials of 2 and 3 are 0.44 V (measured at pH 12) and 1.19 V (measured at pH 7) versus normal hydrogen electrode, respectively, corresponding to the [Fe-IV(O)](2-)/[Fe-III(OH)](2-) and [Fe-V(O)](-)/[Fe-IV(O)](2-) couples. Consistent with its higher potential (even after correcting for the pH difference), 3 oxidizes benzyl alcohol at pH 7 with a second-order rate constant that is 2500-fold bigger than that for 2 at pH 12. Furthermore, 2 exhibits a classical kinteic isotope effect (KIE) of 3 in the oxidation of benzyl alcohol to benzaldehyde versus a nonclassical KIE of 12 for 3, emphasizing the reactivity differences between 2 and 3.

Trapping an elusive Fe(IV)-superoxo intermediate inside a self-assembled nanocage in water at room temperature - Gera, Rahul; De, Puja; Singh, Kundan K.; Jannuzzi, Sergio A. V.; Mohanty, Aisworika; Velasco, Lucia; Kumar, Pankaj; Marco, J. F.; Nagarajan, Kalaivanan; Pecharroman, Carlos; Rodriguez-Pascual, P. M.; DeBBeer, Serena; et al. (JOURNAL OF THE AMERICAN CHEMICAL SOCIETY, 2024)
Keywords: CATALYTIC EPOXIDATION; DIOXYGEN ACTIVATION; NONHEME IRON; X-RAY-ABSORPTION